Carbon nanotube based composites processing, properties, modelling and application - Pantano, Antonio (Smithers Rapra, 2012)
Carbon nanotubes (CNTs) have amazing properties and a key way to take advantage of this is by incorporating nanotubes into a matrix to build composite materials. The best candidates for this task are undoubtedly polymers. Almost every characteristic of a polymer can be significantly enhanced by adding carbon nanotubes and as a result, new potential applications of carbon nanotube enhanced polymer composites are discovered every day. However, before carbon nanotube enhanced polymer composites become commonplace there are some tough challenges that need to be overcome. This book reviews the stat.